Rancang Bangun Virtual Reality (VR) Gerakan Dasar Randai Berbasis 3D sebagai Bentuk Pelestarian Budaya Minangkabau - Haykal Husaini; Fris Okta Falma (MASALIQ, 2026)
Although alumni hold a strategic position as partners of Islamic boarding schools in developing the human resources of santri, scholarly studies on the forms of their contributions and the impacts of their involvement remain limited. This study aimed to analyze the role of alumni in developing and improving the quality of santri human resources at Pondok Pesantren Anwarul Huda Malang. This study employed a qualitative approach with a descriptive design. Informants were selected through purposive sampling and included the pesantren leader and administrators, alumni association administrators, actively contributing alumni, and santri. Data were collected through observation, in-depth interviews, and documentation and were subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña, which comprises data collection, data condensation, data display, and conclusion drawing and verification. The findings showed that alumni played a significant role in improving the quality of santri human resources through five main forms of contribution, namely organizing guidance and skills training, serving as mentors and resource persons based on their professional experience, participating as teachers at Madrasah Diniyah, providing financial support and facilities for pesantren development, and expanding the motivation, perspectives, and career networks of santri. These contributions had positive impacts on improving the knowledge, skills, self-confidence, and readiness of santri to engage in community life and the world of work. This study affirms that alumni involvement and the presence of an active alumni organization are important elements in sustaining synergy between alumni and the pesantren and supporting the continuous development of santri human resources.